Perlindungan Hukum Data Pribadi Anak pada Platform Game Online Berdasarkan UU PDP - Risyad Nur Fadillah; Aturkian Laia (INDO PUBLISHING, 2026)
The high intensity of children playing online games triggers vulnerability to personal data exploitation due to their limited legal capacity to provide informed consent. This legal doctrinal study, employing statutory and conceptual approaches, aims to analyze the potential misuse of children's data, its protection under Law Number 27 of 2022 (UU PDP), and platform responsibilities under Government Regulation Number 17 of 2025 (PP TUNAS). The results indicate that the UU PDP mandates parental consent, while PP TUNAS strengthens this via mandatory age verification, content moderation, and risk-based protection. However, its effectiveness is still hindered by easily manipulated verification mechanisms, a lack of uniform technical processing standards for children's data, and weak oversight of cross-jurisdictional platforms. In conclusion, child data protection requires consistent derivative regulations and optimization of the personal data protection authority's oversight capacity.